2017
DOI: 10.1038/eye.2017.265
|View full text |Cite
|
Sign up to set email alerts
|

Post-LASIK exacerbation of granular corneal dystrophy type 2 in members of a chinese family

Abstract: PurposeThe post-LASIK exacerbation of corneal dystrophy, otherwise asymptomatic, is almost exclusively associated with the TGFBI gene mutations at codon 124 in exon 4 and codon 555 in exon 12. It is our intention to demonstrate that the pre-operative genetic screening for TGFBI mutations should be mandatory for refractive surgery candidates.Patients and MethodsIn this study, we reviewed the proband’s post-LASIK slit-lamp and in vivo confocal microscopy images and genetic testing results, and performed genetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…TGFβI encodes an ECM protein induced by TGFβ that interacts with collagen . Recent studies have shown that mutations in TGFβI in humans cause a condition known as granular corneal dystrophy, which is characterized by opaque deposits in the corneal stroma . Therefore, its upregulation in our data suggests that TGFβI may play a role in organizing collagen fibrils synthesized by the corneal endothelium and keratocytes during early development.…”
Section: Resultsmentioning
confidence: 61%
“…TGFβI encodes an ECM protein induced by TGFβ that interacts with collagen . Recent studies have shown that mutations in TGFβI in humans cause a condition known as granular corneal dystrophy, which is characterized by opaque deposits in the corneal stroma . Therefore, its upregulation in our data suggests that TGFβI may play a role in organizing collagen fibrils synthesized by the corneal endothelium and keratocytes during early development.…”
Section: Resultsmentioning
confidence: 61%
“…Many reports have unfortunately demonstrated the exacerbation of GCD2 after treatment with LASIK (Fig. 2C) (Banning et al, 2006;Chao-Shern et al, 2019;Chao-Shern et al, 2018;Chiu et al, 2007;Jun et al, 2004;Poulsen et al, 2016;Zeng et al, 2017). Therefore, genetic screening for the late onset of heterozygous mutations is recommended before laser refractive procedures, especially in patients with a family history of TGFBI-linked corneal dystrophy (Aldave et al, 2007;Chao-Shern et al, 2019;Chao-Shern et al, 2018;Copeland and Afshari, 2013).…”
Section: Genetic Testing Before Vision Correctionmentioning
confidence: 99%
“…The influence of homozygous R124H mutation on cornea is more seriously affected than heterozygous mutation [4,6,[9][10]13] . Several literature have been reported that corneal deposits in the interface of laser-assisted in situ keratomileusis (LASIK) flap increased postoperatively in the patients with heterozygous ACD initiating 2-5y post-LASIK [3][4][5][10][11][14][15][16][17][18][19][20] , which may cause serious vision loss. Until now, the only method to treat transforming growth factor beta-induced protein (TGFBIp) corneal malnutrition has been a corneal transplant or keratectomy, but the recurrence of protein deposition is unavoidable [9,20] .…”
Section: Introductionmentioning
confidence: 99%